ONLINE GROUP PSYCHODRAMATIC PSYCHOTHERAPY: WARMING-UP REINVENTIONS - Aline Belém (Revista Brasileira de Psicodrama, 2021)
This paper aims to discuss online group psychodramatic psychotherapy practices with an emphasis on warm-up. The hypothesis is that the warm-up step, specifically designed for Online care, contributes to the achievement of a more spontaneous group state. The theoretical north of the work is the warm-up stages proposed by Davoli (1999) from the experience with Spontaneous Theater. Thus, each stage is discussed taking into account the report of some experiences in conducting an online psychotherapy group. From these experiences, we affirm that the warm-up designed for this specific context provides good results in terms of group spontaneity.